Subcutaneous electroencephalography monitoring for people with epilepsy and intellectual disability: co-production workshops - Edward Meinert; Madison Milne-Ives; Jennifer Sawyer; Liz Boardman; Sarah Mitchell; Brendan Mclean; Mark Richardson; Rohit Shankar (BJPsych Open)
Background Nearly 25% of people with intellectual disability (PwID) have epilepsy compared to 1% of the UK general population. PwID are commonly excluded from research, eventually affecting their care. Understanding seizures in PwID is particularly challenging because of reliance on subjective external observation and poor objective validation. Remote electroencephalography (EEG) monitoring could capture objective data, but particular challenges and implementation strategies for this population need to be understood.